ECONOMIC DEVELOPMENT PATTERNS AND REGIONAL INEQUALITY IN DISTRICTS AND CITIES OF WEST SUMATERA PROVINCE - Wenny Wahyudi; Era Triana; Nori Yusri; Vivi Ariani (Fakultas Teknik Sipil dan Perencanaan. Universitas Bung Hatta, 2024)
Uneven regional development may lead to disparities in economic performance across regions. West Sumatra Province, which consists of seven cities and twelve regencies, exhibits diverse economic, demographic, and natural resource characteristics that contribute to variations in regional development. This study aims to analyze patterns of economic development and the level of regional inequality among districts and cities in West Sumatra Province during the period 2011–2019. The analysis employs the Klassen typology to classify regional economic growth patterns and the Williamson Index to measure the degree of regional inequality. Secondary data on Gross Regional Domestic Product (GRDP) and GRDP per capita were obtained from the Central Bureau of Statistics. The results of the Klassen typology analysis indicate that most cities in West Sumatra Province fall into the category of advanced and rapidly growing regions, while several regencies are classified as developed but depressed, fast-growing, or relatively lagging regions. Furthermore, the Williamson Index results show that regional inequality in West Sumatra Province during the study period remains at a low level and tends to approach zero, suggesting that economic growth and development across regions are relatively even.